Role of Low-Leve Nitrogen Laser Therapy in Tubercular Cold Abscess Not Responding to Surgery & Chemotherapy (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2011)
Background: Tubercular empyema is one of the commonest chronic diseases in the developing countries of the world including India. As the problem of drug resistant strain of tubercular bacilli is increasing, new modalities of treatment that could act against resistant strain are needed. Objective: The purpose of this study was to evaluate the efficacy of low- level nitrogen laser therapy (LLLT) as an adjuvant to anti-tubercular treatment in case of tubercular empyema that was not responding to conventional anti-tuberculosis drugs and repeated pus aspiration. Patient: The patient, a 19 year old male was diagnosed with tubercular empyema. He was not improving by conventional treatment and pus aspiration. The patient was administered intralesional nitrogen laser (337 nanometer, average power 5 mW) for 780 seconds at intervals of 72 hours up to 10 weeks. Results: After the fifth laser irradiation session, decrease in chest pain was reported and pus mixed with blood pleural fluid aspirated. After the tenth laser irradiation session, serous pleural fluid was aspirated. After 20 sessions of laser irradiation the empyema was healed completely and the patient also regained almost complete expansion of lung. Conclusion: LLLT was observed to results in the healing of the tubercular empyema and also found to make the empyema free of Mycobacterium tuberculosis. However, further randomized studies with more patients are needed to prove the efficacy of this method. Key words: Mycobacterium tuberculosis; empyema; laser  DOI: 10.3126/saarctb.v7i2.4402SAARC J. TUBER. LUNG DIS. HIV/AIDS 2010 VII(2) 26-29